2019
DOI: 10.1111/hex.12979
|View full text |Cite
|
Sign up to set email alerts
|

What motivates patients and caregivers to engage in health research and how engagement affects their lives: Qualitative survey findings

Abstract: Background US research organizations increasingly are supporting patient and stakeholder engagement in health research with a goal of producing more useful, relevant and patient‐centered evidence better aligned with real‐world clinical needs. The Patient‐Centered Outcomes Research Institute (PCORI) engages patients, family caregivers and other health‐care stakeholders, including clinicians, payers and policymakers, as active partners in prioritizing, designing, conducting and disseminating research as a key st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(74 citation statements)
references
References 20 publications
(62 reference statements)
6
66
0
Order By: Relevance
“…POs mainly concentrate on educating patients, physicians, and the community about disease and management and treatment innovation; championing and directly funding efforts to increase disease comprehension and develop new therapies; forming connections between disease key opinion leaders and drug companies; and providing drug developers with relevant insights into the patient community to facilitate the development of therapies that best meet the community’s needs [ 91 , 92 ].…”
Section: Resultsmentioning
confidence: 99%
“…POs mainly concentrate on educating patients, physicians, and the community about disease and management and treatment innovation; championing and directly funding efforts to increase disease comprehension and develop new therapies; forming connections between disease key opinion leaders and drug companies; and providing drug developers with relevant insights into the patient community to facilitate the development of therapies that best meet the community’s needs [ 91 , 92 ].…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, it is important for patient partners, to be able to link their involvement in a given research project to its impact for their community. For instance, a recent study found that the main impetus for patient partners engagement in research is benefiting others [37]. In the case of Indigenous patient partners in our initiative, this altruistic motivation was specifically oriented towards their cultural community.…”
Section: Discussionmentioning
confidence: 95%
“…Patients likely experience physical or emotional impairments such as fears, grief, and anxiety while using the service [86]. All of these factors likely suggest that a particular patient's informational and decision-making needs are different from those that they would have outside of a health care context [86][87][88][89]. Patient participation and active engagement are the classic tenets of task, user, representation, and functional analysis used to inform system designers and leadership that are contemplating implementing solutions to patient-centered problems [87][88][89].…”
Section: Xsl • Fomentioning
confidence: 99%